Nurse Staffing, Missed Care, and Risk of Patient Mortality. Issue 2 (March 2022) - Simpson, Kathleen Rice
Abstract : Perinatal patient safety depends on adequate nurse staffing. When nurses are working short-staffed, essential aspects of nursing care can be missed, which increases risk of adverse patient outcomes. Examples of risks of patient morbidity and mortality associated with missed nursing care are presented.